A rare presentation of amyloid goiter with renal amyloidosis in a young female - Sriharsha, Tirumalasetty; Raj J., Raghav; Venkatesan, Sudha; Reddy, Nooka M.; V., Vikrannth; Raghavan, Vinod; Rajendran, Kannan (International Journal of Advances in Medicine, 2023)
Amyloidosis is a rare systemic disorder caused by abnormal folding of normal soluble proteins leading to fibril formation in one or more body organs, systems or soft tissues. Amyloid goiter is characterized by deposits of amyloid protein in the thyroid tissue. Amyloid infiltration of thyroid gland with development of secondary goiter is rare. Here we report a case of 36-year-old female presented with progressive painless swelling over neck. Thyroid profile was normal. Ultrasound neck showed enlarged bilateral thyroid gland and isthmus. Fine needle aspiration cytology suggestive of subacute thyroiditis (granulomatous thyroiditis). Total thyroidectomy was done and biopsy sample revealed amyloid goiter.